The misalignment between accounting faculty perceptions of success and organizational image during a process of institutional change - Nova, S. C.; Azevedo, R.; Lourenço, I. (40th European Accounting Association Annual Congress, 2017)
This study analyzes the impacts of an institutional change process on a specific higher education institution from a European country, and the trade-offs between the faculty perceptions of success and the organization image during this process. Known as a center of excellence in academic teaching and executive education, and well-positioned in international rankings, the Institute began a significant reorganization process that included, among other features, changes in the governance rules of each department and the implementation of a hiring, tenure and promotion policy. Under this policy, faculty members began to be formally evaluated, compared and assessed with a focus on their scientific publications, mainly on the outcomes of their research activities (publication outputs in top journals). The impacts of this policy are analyzed and discussed based on in-depth interviews conducted with faculty members of the Accounting Department in which they reflected upon academic success vis-a-vis the career assessment system adopted, followed up by those faculty members’ answering an electronic questionnaire about organizational identity and image perception (Gioia, Schultz, & Corley, 2000). Considering the individual perspectives, faculty are concerned about their vocations and aspirations, with feelings of apprehension and insecurity (Knights and Clarke, 2014; Harding, Ford, & Gough, 2010; Gendron, 2008). The institutional goals are perceived as too high and potentially unattainable. They also perceive that by shifting the priority towards research, costs in terms of losing the institutional excellence in teaching might arise, which has been traditionally keen to the Institute’s organizational identity and consistent with faculty member’s perceptions of academic success (Hoskins, 2010; 2012). Our argument is that this conflict is a multilevel phenomenon, wherein individual academic identities are in conflict with institutional image. Our study entails a contribution to the application of the identity institutional theory to academic institutions.